Acts of rebellion : the Ward Churchill reader - Churchill, Ward. (New York : Routledge, 2003)
What could be more American than Columbus Day? Or the Washington Redskins? For Native Americans, they are bitter reminders that they live in a world where their identity is still fodder for white society. ""The law has always been used as toilet paper by the status quo where American Indians are concerned, "" writes Ward Churchill in Acts of Rebellion, a collection of his most important writings from the past twenty years. Vocal and incisive, Churchill stands at the forefront of American Indian concerns, from land issues to the American Indian Movement, from government repression to the histor.
"The law stood squarely on its head" -- The nullification of Native America? -- Confronting Columbus Day -- The earth is our mother -- A breach of trust -- Like sand in the wind -- The bloody wake of Alcatraz -- Fantasies of the master race -- Let's spread the "fun" around -- Indians 'R' us -- False promises -- The new face of liberation -- I am indigenist.
Includes bibliographical references (pages 303-447) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Indians of North America -- Government relations; Indians of North America -- Social conditions; Indians of North America -- Land tenure; Indian land transfers; Indians -- Land tenure; Peuples autochtones -- Terres; Peuples autochtones -- États-Unis -- Relations avec l'État.; SOCIAL SCIENCE -- Ethnic Studies -- Native American Studies; Indians -- Land tenure; Indian land transfers; Indians of North America -- Government relations; Indians of North America -- Land tenure; Indians of North America -- Social conditions; Electronic book; Electronic books